The Impact of E-Service Quality and Price on Customer Satisfaction of Tokopedia - Abdillah Taufikqurrochman; Ratih Juliati; Sandra Irawati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The purpose of this study is to determine and analyze the impact of e-service quality and price on customer satisfaction in e-commerce Tokopedia. This type of research is explanatory research. The population in this study is the people in Malang Raya who buy in Tokopedia. The sample in this study amounted to 100 respondents and the sampling technique used purposive sampling. The data source in this study was the primary data source. Data collection techniques using a survey method with a questionnaire. Data analysis techniques in this study are multiple regression analysis with t-test, f test, and dominant test. The results of this study indicate that the better the e-service quality, the higher the level of customer satisfaction, the cheaper the price offered, the higher the level of customer satisfaction, other than that the result indicates that the variable simultaneous e-service quality and price have a positive effect on the customer satisfaction and variable e-service quality have a dominant influence on customer satisfaction in e-commerce Tokopedia.